Characteristics for Functional Brain Asymmetry of Children With Pseudobulbar Dysartria - Arefieva, A (KnE Life Sciences, 2018)
The article raises important problem of the causes of functional brain asymmetry and interhemispheric interaction of children with pseudobulbar dysarthria. The left hemisphere is dominant in relation to speech function for the absolute majority of people. Therefore, the physiological process for forming distribution of functions between hemispheres in ontogeny is important not only from the point of the correct speech development as the highest mental function but also reflects on the wide spectrum of psyche features, perception and cognitive processes, adaptive capabilities of the organism, control over involuntary behavior. There are 40 children with a normal speech development and with a clinical diagnosis of ‘pseudobulbar dysarthria’, determine a lateral phenotype, calculate coefficients of functional asymmetry, and the most common types of violations identify of higher cortical functions. Confirmed information on the prevalence for the right hemispheric dominance among children with speech disorders. The most common types of violations in higher cortical functions are the failure of phonemic analysis and auditory memory. Keywords: functional asymmetry, interhemispheric actions, children, pseudobulbar dysarthria